A general strategy for the synthesis of homogeneous hyaluronan conjugates and their biological applications. Issue 25 (13th March 2017) - Fu, Xuan; Shang, Wenjing; Wang, Shuaishuai; Liu, Yunpeng; Qu, Jingyao; Chen, Xi; Wang, Peng George; Fang, Junqiang
Abstract : Here, we developed a general strategy for synthesizing homogeneous HA conjugates, and generated homogeneous HA– p NP, HA–biotin, and HA–oroxylin conjugates to investigate the relationships between HA chain length and its diverse biological functions. Abstract : Here, we developed a general strategy for synthesizing homogeneous HA conjugates, and generated homogeneous HA– p NP, HA–biotin, and HA–oroxylin conjugates to investigate the relationships between HA chain length and its diverse biological functions.